2012
DOI: 10.1016/j.pain.2011.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Insomnia, sleep quality, pain, and somatic symptoms: Sex differences and shared genetic components

Abstract: This study investigated the sex differences, and the shared genetic and environmental factors underlying the associations of sleep disturbances (insomnia and sleep quality) with pain and somatic symptoms in both adolescents and middle-aged adults. We recruited 259 adolescents (69 with current insomnia) and their parents (256 middle-aged adults, 78 with current insomnia). Insomnia severity and sleep quality were measured by the Insomnia Severity Inventory (ISI) and Pittsburgh Sleep Quality Index (PSQI), respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
64
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(75 citation statements)
references
References 44 publications
8
64
1
2
Order By: Relevance
“…That study reported robust associations of the ISI with the severity of pain and non-pain somatic complaints over the prior week, after controlling for the Hospital Anxiety and Depression Scale scores (48) which overlap in content with the distress, anxiety and depression subscales of the 4-DSQ. In conclusion, our result with respect to somatic complaints within 1 week can be regarded as corroborating the finding of Zhang et al (15), whereas the result on pain intensity generalizes their finding to a longer reference period (up to 6 months).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…That study reported robust associations of the ISI with the severity of pain and non-pain somatic complaints over the prior week, after controlling for the Hospital Anxiety and Depression Scale scores (48) which overlap in content with the distress, anxiety and depression subscales of the 4-DSQ. In conclusion, our result with respect to somatic complaints within 1 week can be regarded as corroborating the finding of Zhang et al (15), whereas the result on pain intensity generalizes their finding to a longer reference period (up to 6 months).…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, different sets of psychological symptoms (or none at all) were controlled for in different studies, making comparisons somewhat difficult. The most similar study to the current one, but of a smaller scale, was conducted by Zhang et al (15). That study reported robust associations of the ISI with the severity of pain and non-pain somatic complaints over the prior week, after controlling for the Hospital Anxiety and Depression Scale scores (48) which overlap in content with the distress, anxiety and depression subscales of the 4-DSQ.…”
Section: Discussionmentioning
confidence: 74%
“…An added complication is that commonly comorbid depression or anxiety symptoms may better account for poor sleep quality in individual with chronic pain than pain symptoms (27). However, populations with insomnia (28) or migraine (29) maintain the pain-poor sleep quality relationship after controlling for depression so the influence of depression and anxiety on the association between poor sleep quality and pain may depend on the clinical population being studied (8). …”
Section: Discussionmentioning
confidence: 99%
“…14 Furthermore, poor sleep health, such as insomnia, has been associated with greater sensitivity to pain. 15 That said, many inconsistencies are evident in the risk of development, severity, frequency, and duration of headache between females and males and whether there is a gender difference in effects of chronic headache. 13,[16][17][18] Furthermore, the interaction of chronic headache, sleep insufficiency, and gender, to our knowledge, has not been well studied especially in the adolescent population.…”
Section: Introductionmentioning
confidence: 99%